Peningkatan Kompetensi Kaidah Bahasa Arab bagi Pemula Menggunakan Al-Tadrībāt Al-Lughawīyah - Ibnu Rawandhy N. Hula (Universitas Islam Negeri Palangka Raya, 2020)
This research study is classified as field research with quasi experimental method. The study aims to find out the ability level of the students of Arabic Department graduated non-Islamic Boarding School in doing linguistic exercises (al-Tadriba t al-Lugawiyah) which consists of 12 topics. The steps of the experiment method were started from 1) population, 2) sample, 3) giving materials, 4) giving practice test, 5) data collection (results), 6) data Analysis/ results, and 7) conclusions. The research study